Problem Mendasar Yang Muncul Dari Perkembangan Ilmu Di Bidang Hukum - Wawan Irawan (Fakultas Hukum, Universitas Islam Bandung, 2017)
Recording the history of science can be traced back to thousands of years before Christ until now. Historical necessity gave birth to a wide range of concepts about the nature of science. Law as science has a distinctive character (suigeneris), that it is normative. Those characteristics caused some law scholars that do not understand the characteristics of jurisprudence have doubted law as a science. Doubt it caused more normative jurisprudence rather than empirical and his study object with respect to the guidance of behavior in a way that compliance is not entirely dependent on free will is concerned, but can be imposed by a public authority.Through science we generate new knowledge. Since the beginning of human civilization, Law has progressed in a continuous process. Progress toward understanding and managing the law-science problem seems to require disaggregating the questions. If we look carefully at what kind of